Executive Orders - Clancy, Tom (London Harper Collins Publisher, 1996)
After an airliner crashes into the Capitol, killing the president, Jack Ryan, the vice-president takes over. The novel describes Ryan's campaign to impose a right-wing morality on the U.S. and a new order on the world, the latter accomplished with the aid of high-tech warfare. A sequel to Debt of Honor. Jack Ryan becomes president by sheer accident when the former president, most of Congress, the Cabinet and the Supreme Court are bombed out of existence. Ryan must jump in to discover who did it, all the while contending with the threat of military takeover and covert biological warfare.
Keywords: United States